2019
DOI: 10.1177/2045125319845774
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic hallucinogens and recognition of facial emotion expressions: a systematic review of the literature

Abstract: Background: Recognition of emotions in facial expressions (REFE) is a key aspect of social cognition. Anxiety and mood disorders are associated with deficits in REFE, and anxiolytics and antidepressants reverse these deficits. Recent studies have shown that serotonergic hallucinogens (i.e. ayahuasca, dimethyltryptamine, psilocybin, lysergic acid diethylamide [LSD], and mescaline) have anxiolytic and antidepressant properties, but their effects on REFE are not well understood. The purpose of the study was to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 31 publications
6
43
0
2
Order By: Relevance
“…There is a growing body of evidence to suggest serotonergic hallucinogens can affect recognition of facial expressions (Rocha et al., 2019). LSD has been shown to reduce recognition of sad or fearful faces alongside enhancing emotional empathy (Dolder et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence to suggest serotonergic hallucinogens can affect recognition of facial expressions (Rocha et al., 2019). LSD has been shown to reduce recognition of sad or fearful faces alongside enhancing emotional empathy (Dolder et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For MM, repeated training promotes the use of mental strategies, altering the cognitive frame in which negative thoughts are perceived and coped with (e.g., 133). With regard to psilocybin, perceptual and thought contents are directly altered by destabilizing established belief systems resulting in a restoration of adequate mood regulation (e.g., 69,172,173).…”
Section: Moodmentioning
confidence: 99%
“…Psychedelics have also been shown to alter the recognition of negative faces and reduce amygdala reactivity to negative faces, with a number of studies finding associations between acute and post-acute attenuations of amygdala reactivity to negative faces and post-acute increases in positive mood and well-being. 63 66 Another study, however, found that increased amygdala responses compared to baseline for fearful and happy faces 1 day after psilocybin correlated with decreases in depressive symptoms. 67 In contrast to these prior results, a recent study found no acute or post-acute effects of ayahuasca on FER compared to placebo.…”
Section: Introductionmentioning
confidence: 99%